ORGANIZING COVID-19 SURVIVORS AS CONVALESCENT PLASMA DONORS - Erwin Astha Triyono; Rimbun Rimbun (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: Convalescent plasma transfusion therapy remains as one of the therapies recommended by the Ministry of Health for Covid-19 patients in Indonesia. However, in its practice, this therapy is greatly constrained by the availability of plasma donors at the Indonesian Red Cross (PMI) and the few survivors who are willing to donate their blood plasma. The aims of the community service activity were to educate, organize, and facilitate the survivors to do screening and donate their plasma. Methods: The activities were conducted in June until December 2021, at Indrapura Field Hospital (RSLI) Surabaya. A total 925 participants (641 male and 309 female) were all Covid-19 patients from RSLI Surabaya. The demographic data were collected and organized as a database. The survivor's online communication group (16 WhatsApp groups) were created, to provide information and education about Covid-19 and the importance of plasma donation to the patients and survivors. Results: The three largest groups by age were 26-35 (30.84%), 46-55 (21.26%), and 36-45 (19.47%) years old. The 3 largest groups by city of origin were Surabaya (62.42%), Sidoarjo (16.53%), and Gresik (8.63%). About 77.89% of participants have their understanding in the convalescent plasma for Covid-19. About 43.79% of them were willing to become donors after 14-day-recovery, and have been registered in the web application of donors. The 102 survivors were also involved in free plasma screening with PMI Surabaya. Total 88 survivors who have passed the screening have given their plasma as convalescent donors. Conclusion: Organizing and educating Covid-19 survivors were exceptionally required to encourage them to become a plasma donor. The collected survivor data must be stored and managed properly to facilitate everything related to the blood plasma. The survivors are suggested to be screened 14 days after being declared healthy, to maintain the availability of blood plasma at PMI for Covid-19 patients who necessitate the convalescent plasma therapy.